Caught in the Crossfire: Aggression and Violence against Doctors in Pakistan after 9/11 - Rubeena Zakar, Shazia Qureshi, Muhammad Zakria Zakar, Ashraf Chaudry, Nauman Aqil, Safdar Abbas, Saeed Watto (Journal of Political Studies, 2014)
In the backdrop of 9/11 and war against terror in Afghanistan, Pakistani society has witnessed recurrent episodes of conflict and violence. The level of intolerance has substantially increased and use of violent means has become a norm. While citizens across the board have suffered from rising insecurity, doctors have particularly been the victim of violence. This study intended to investigate the extent of violence committed against the doctors in the hospital settings, their coping strategies, and emotional sufferings due to their violence experiences. For data collection, cross sectional survey was conducted with 200 randomly selected doctors in four randomly selected teaching hospitals of Lahore. The data revealed that house officers were most vulnerable to violence in the hospital setting among the doctors. Significant gender variations were observed and male doctors reported to have suffered more form violent acts as compared to female doctors. Doctors mostly used passive coping strategies against violence and reporting to police was the least cited response. They felt angry over these incidents but reported to feel helpless about the situation. The study concluded that the root of problem lies in the inefficient health care system and the lack of capacity to cater the needs of population. It is suggested that the healthcare system in the country may be strengthened to the satisfaction of patients and his/her relatives so that the doctors may be protected against the aggression of disgruntled people.